The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.05.09.491127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The endothelial-specific LINC00607 mediates endothelial angiogenic function

Abstract: Long non-coding RNAs (lncRNAs) can act as regulatory RNAs which, by altering the expression of target genes, impact on the cellular phenotype and cardiovascular disease development. Endothelial lncRNAs and their vascular functions are largely undefined. Deep RNA-Seq and FANTOM5 CAGE analysis revealed the lncRNA LINC00607 to be highly enriched in human endothelial cells. LINC00607 was induced in response to hypoxia, arteriosclerosis regression in non-human primates and also in response to propranolol used to in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The top tag SNP, rs78529201, falls within an intron of the lincRNA, LINC00607 . Bulk tissue gene expression results from the Genotype-Tissue Expression portal (GTEx Portal) show the tissue with the highest expression of LINC00607 are arteries (Sriram et al, 2022) and another recent study demonstrated it is highly enriched in endothelial cells (Boos et al, 2022). Previous work has shown a key role of LINC00607 in the control of cellular processes underlying inflammatory responses, angiogenesis, collagen catabolism and extracellular matrix organization in endothelial cells via its inactivation of PAI-1 , an inhibitor of plasminogen activators (Calandrelli et al, 2019; Sriram et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top tag SNP, rs78529201, falls within an intron of the lincRNA, LINC00607 . Bulk tissue gene expression results from the Genotype-Tissue Expression portal (GTEx Portal) show the tissue with the highest expression of LINC00607 are arteries (Sriram et al, 2022) and another recent study demonstrated it is highly enriched in endothelial cells (Boos et al, 2022). Previous work has shown a key role of LINC00607 in the control of cellular processes underlying inflammatory responses, angiogenesis, collagen catabolism and extracellular matrix organization in endothelial cells via its inactivation of PAI-1 , an inhibitor of plasminogen activators (Calandrelli et al, 2019; Sriram et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Fine-mapping at this locus implicated a tag SNP rs78529201 located within long intergenic non-coding RNA (lincRNA) LINC00607 . Existing literature highlights LINC00607 as a super enhancer in a gene expression network that is critical for regulation of normal endothelial cell function as well as dysfunction, suggesting a putative link of the 2q35 locus to PAD etiology (Calandrelli et al, 2019; Boos et al, 2022; Sriram et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The top tag SNP, rs78529201, falls within an intron of the lincRNA, LINC00607. Bulk tissue gene expression results from the Genotype-Frontiers in Genetics frontiersin.org Tissue Expression portal (GTEx Portal, 2022) show the tissues with the highest expression of LINC00607 are arteries (Sriram et al, 2022), and another recent study demonstrated that it is highly enriched in endothelial cells (Boos et al, 2022). Previous work has shown a key role of LINC00607 in the control of cellular processes underlying inflammatory responses, angiogenesis, collagen catabolism, and Frontiers in Genetics frontiersin.org extracellular matrix organization in endothelial cells via its inactivation of PAI-1, an inhibitor of plasminogen activators (Calandrelli et al, 2019;Sriram et al, 2022).…”
Section: Fine-mapping the 2q35 Locusmentioning
confidence: 99%